2021
DOI: 10.1186/s13690-021-00609-0
|View full text |Cite|
|
Sign up to set email alerts
|

Utilization of preventive care among migrants and non-migrants in Germany: results from the representative cross-sectional study ‘German health interview and examination survey for adults (DEGS1)’

Abstract: Background In Germany, different health checks for adults are offered for primary and secondary prevention. Previous findings indicate that preventive care utilization varies according to social determinants, especially migration background. This study examined the extent to which migration background is associated with preventive care utilization, independent of factors like age and socioeconomic status and whether length of stay in Germany has a positive effect on the use of preventive care. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
10
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 40 publications
2
10
0
4
Order By: Relevance
“…O fenômeno migratório é um determinante independente da saúde que interage com outros fatores socioeconômicos e culturais. 23,24 Revisões sistemáticas apontam que a relação entre as condições sociodemográficas e a saúde é mais acentuada para os migrantes do que para a população nativa, 26,27 visto que situações precárias de vida e trabalho, limitação no idioma do país receptor, etnia, escolaridade e falta de familiarização com o sistema de saúde, por ser recém-chegados, podem gerar limitações e diferenças no uso dos serviços de cuidados à saúde, contribuindo para o aumento de efeitos deletérios ao estado de saúde físicae mental do imigrante, [28][29][30] o que reforça o olhar quanto aos riscos de saúde do grupo IMB.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…O fenômeno migratório é um determinante independente da saúde que interage com outros fatores socioeconômicos e culturais. 23,24 Revisões sistemáticas apontam que a relação entre as condições sociodemográficas e a saúde é mais acentuada para os migrantes do que para a população nativa, 26,27 visto que situações precárias de vida e trabalho, limitação no idioma do país receptor, etnia, escolaridade e falta de familiarização com o sistema de saúde, por ser recém-chegados, podem gerar limitações e diferenças no uso dos serviços de cuidados à saúde, contribuindo para o aumento de efeitos deletérios ao estado de saúde físicae mental do imigrante, [28][29][30] o que reforça o olhar quanto aos riscos de saúde do grupo IMB.…”
Section: Discussionunclassified
“…Em relação às DCNTs, não diferiram entre os grupos de países por renda per capita, exceto a gastrointestinal, mas os IAL possuem aproximadamente duas vezes mais chances de ter alguma DCNT, sendo a mais citada a hipertensão arterial sistêmica, assim como para os indivíduos mais velhos do estudo, independentemente do grupo de países.Achados do presente estudo também apontam que as mudanças de percepção em relação às condições de saúde pós-migração estão associadas à idade e ao tempo de permanência, e corroborando outros estudos, 12,22,30 inclusive para surgimento de doenças crônicas. 31,32 Saúde de imigrantes no nordeste do Brasil Aragão HT, Menezes AN, Oliveira MLL, Santana JT, Madi RR, Melo CM Os imigrantes adentram o país receptor com melhores condições de saúde do que a população não imigrante, o denominado "efeito do imigrante saudável".…”
Section: Discussionunclassified
“…The observed convergence of disease incidence over time could be partially explained by medical underuse in the country of origin and direct access to medical care in Germany after immigration. However, a survey showed that despite direct access to the German health care system, resettlers tend not to participate in offered preventive and screening examinations [ 35 , 36 ]. Studies have shown that cancer and cardiovascular disease rates of migrants adapt to rates of the host country [ 37 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Specific frail groups in society, such as women with a migrant background seem to be confronted with significantly more impediments for taking up preventive measures and should therefore be specially considered [ 21 ]. Language barriers, poor working conditions, and low social status could increase the health risks for many migrant women [ 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%